Single‐Cell Quantification of a Highly Biocompatible Dinuclear Iridium(III) Complex for Photocatalytic Cancer Therapy. (6th April 2022) - Fan, Zhongxian; Rong, Yi; Sadhukhan, Tumpa; Liang, Shaoxia; Li, Wenqing; Yuan, Zhanxiang; Zhu, Zilin; Guo, Shunwen; Ji, Shaomin; Wang, Jinquan; Kushwaha, Rajesh; Banerjee, Samya; et al.
Abstract: Quantifying the content of metal‐based anticancer drugs within single cancer cells remains a challenge. Here, we used single‐cell inductively coupled plasma mass spectrometry to study the uptake and retention of mononuclear (Ir1 ) and dinuclear (Ir2 ) Ir III photoredox catalysts. This method allowed rapid and precise quantification of the drug in individual cancer cells. Importantly, Ir2 showed a significant synergism but not an additive effect for NAD(P)H photocatalytic oxidation. The lysosome‐targeting Ir2 showed low dark toxicity in vitro and in vivo . Ir2 exhibited high photocatalytic therapeutic efficiency at 525 nm with an excellent photo‐index in vitro and in tumor‐bearing mice model. Interestingly, the photocatalytic anticancer profile of the dinuclear Ir2 was much better than the mononuclear Ir1, indicating for the first time that dinuclear metal‐based photocatalysts can be applied for photocatalytic anticancer treatment. Abstract : Single‐cell plasma mass spectrometry was applied for the rapid, label‐free quantification of a dinuclear Ir III photocatalyst at the single‐cell level. Ir2 exhibited high cellular uptake and retention efficiency along with long‐wavelength light absorption. In vivo, biocompatible Ir2 showed a lysosome‐targeting multimodal anticancer mechanism of action via its unique photocatalytic oxidation of amino acids and the co‐enzymes NAD(P)H.